Unequal Developments in Indonesia’s Digital-Based Economy and Its Implications - Sri Adiningsih; Stri Nariswari Setiaji; Sofian Rendy Ardiansyah (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2019)
Despite having emerged for just some years, the development and growth of the digital-based economy in Indonesia is exponential. This study uses the Purposive Random Sampling and Descriptive Analyses method to assess the developments of the digital-based economy in several provinces in Indonesia. The Java-Bali region is more advanced in its digital-based economy compared to other provinces in Indonesia due to its infrastructure, human resources, and government policies which are more supportive. The inequalities between provinces remain a concern for it may directly correlate to a corresponding increase in disparity. Digital-based economy, if it is well-equipped with infrastructure and well-supported by local government, may serve as a balm given its potential as a tool to raise prosperity and equality in society. It will help prepare and equip those in remote rural areas, known as the bottom of the pyramid.